Kinerja KPU Kabupaten Buleleng dalam Aksesibilitas bagi Pemilih Disabilitas untuk Meningkatkan Partisipasi pada Pemilu Serentak 2024 - Ningsih, Ni Luh Putu Melia; Yudartha, I Putu Dharmanu; Prabawati, Ni Putu Anik (Socio-political Communication and Policy Review, 2025)
This study uses a type of qualitative research with a descriptive approach. The data sources used are primary and secondary data. The technique for determining informants in this study uses purposive sampling. This study uses the theory of measuring the performance of public organizations according to Agus Dwiyanto in Pasolong (2017). The results of the study show that the performance of the Buleleng Regency KPU in accessibility for voters with disabilities to increase participation in the implementation of the 2024 simultaneous elections is quite good, which is based on productivity indicators that are not optimal so that there is a need to improve the quality of human resources which affects the achievement of activity goals that are not optimal. Service quality indicators are not optimal, there is a need to improve service quality in physical accessibility. The responsiveness indicator has not been optimal, for which the Democracy Volunteer Program has not been implemented. Indicators of responsibility and accountability are optimal. Based on the results of the analysis of the findings, the researcher recommends increasing the number of employees of the Buleleng Regency KPU and developing the competencies of the Ad-Hoc Agency through training, involvement of volunteers with disabilities, expanding cooperation between parties and written cooperation, implementing the Democracy Volunteer program, and involving people with disabilities as election organizers. Abstrak Penelitian ini mengunakan jenis penelitian kualitatif dengan pendekatan deskriptif. Sumber data yang digunakan yaitu data primer dan sekunder. Teknik penentuan informan dalam penelitian ini menggunakan purposive sampling. Penelitian ini menggunakan teori pengukuran kinerja organisasi publik menurut Agus Dwiyanto dalam Pasolong (2017). Hasil penelitian menunjukkan kinerja KPU Kabupaten Buleleng dalam aksesibilitas bagi pemilih disabilitas untuk meningkatkan partisipasi pada penyelenggaraan Pemilu serentak 2024 cukup baik, yang didasarkan pada indikator produktivitas belum optimal sehingga perlu adanya peningkatan kualitas SDM yang berpengaruh pada tidak optimalnya pencapaian sasaran kegiatan. Indikator kualitas layanan belum optimal, perlu adanya peningkatan kualitas layanan pada aksesibilitas fisik. Indikator responsivitas belum optimal, yang mana Program Relawan Demokrasi tidak terlaksana. Indikator responsibilitas dan akuntabilitas sudah optimal. Berdasarkan hasil analisis hasil temuan, peneliti merekomendasikan penambahan jumlah pegawai KPU Kabupaten Buleleng dan pengembangan kompetensi Badan Ad-Hoc melalui pelatihan, pelibatan relawan disabilitas, melakukan perluasan kerja sama antar pihak dan kerja sama tertulis, melaksanakan program Relawan Demokrasi, dan melibatkan penyandang disabilitas sebagai petugas penyelenggara Pemilu. Kata kunci: Kinerja, KPU Kabupaten Buleleng, Aksesibilitas, Disabilitas, Pemilu serentak 2024